Advanced waste heat harvesting strategy for marine dual-fuel engine considering gas-liquid two-phase flow of turbine. (1st June 2021) - Ouyang, Tiancheng; Su, Zixiang; Yang, Rui; Wang, Zhiping; Mo, Xiaoyu; Huang, Haozhong
Abstract: The depletion of fossil fuel reserves and deterioration of ecological environment have brought unprecedented challenges to marine manufacturers under the prevailing global trade. To alleviate the severe situation and comply with the concept of energy-conservation and emission-reduction, the development of green, efficient and sustainable waste heat recovery technology is imperative. Here, we propose an advanced waste heat harvesting strategy considering two-phase flow simulation and energy deployment for marine dual-fuel engine. Significantly, the mechanism of bubble formation and its effect on the system are discussed. Subsequently, the relationships between the working-fluid and sensitivity parameters to the subsystem performance are analyzed. Interestingly, a parallel system is designed to dynamically control and deploy energy in coping with the marine real-time energy demand. After the multi-objective optimization, the thermodynamic, economic and environmental performance of the multistage system are calculated. The results prove that (i) the multistage system can recover the investment cost in 10.71 years, the output-power, cooling-capacity and fresh-water are 278.87 kW, 28.96 kW and 0.24 kg/s, respectively; (ii) compared with the original engine system, the output-power and thermal-efficiency of the engine-multistage system are increased by 287.6 kW and 6.89%, showing excellent thermodynamic performance. Graphical abstract: Image 1 Highlights: An advanced waste heat harvesting strategy for marine dual-fuel engine is proposed. The influence of bubbles in two-phase flow on system performance is considered. Parallel system is designed to deal with the real-time energy demand in the marine. The optimal thermoeconomic conditions are determined by multi-objective optimization. The output power, thermal and exergy efficiencies reach 287.6 kW, 30.2% and 63.3%.